Measurement of uranium concentration in soil samples by two different methods - Baykara, O.; Kulahci, F.; Dogru, M. (Springer, 2007)
In the present work, uranium concentration was determined in 15 soil samples by using CR-39 nuclear track detector and NaI(Tl) gammaspectroscopy. Obtained data are compared.
Keywords: Radon; Thoron; Ssntd